Learning Activities of the of Students in Peer-Jury Practices in the Architecture Design Studio - Rahman Tafahomi (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The students learn through critical thinking and commenting on the design works of other students. This paper aims to demonstrate the students' learning process in a peer-jury activity through both mind engagement and practical activities in the architecture design studio. The methodology of the research was based on qualitative methods with the application of semi-structured observation, photography, sketching, and graphical analysis techniques. The findings of the analysis reveal that the students participated in the peer-jury activity with five attitudes including passive, reactive, active, interactive, and engaged. The peer-jury groups’ applied four approaches to comment on the peer presenters' design outputs, including the design process, task response, idea of the design, and design outputs. In conclusion, the students learn through peers effectively to enhance their skills and abilities in a structured communication. The students improve critical thinking skills through practice, personalization, and communication.